Glutathione "Redox Homeostasis" and Its Relation to Cardiovascular Disease. (9th May 2019) - Bajic, Vladan P.; Van Neste, Christophe; Obradovic, Milan; Zafirovic, Sonja; Radak, Djordje; Bajic, Vladimir B.; Essack, Magbubah; Isenovic, Esma R.
Abstract : More people die from cardiovascular diseases (CVD) than from any other cause. Cardiovascular complications are thought to arise from enhanced levels of free radicals causing impaired "redox homeostasis, " which represents the interplay between oxidative stress (OS) and reductive stress (RS). In this review, we compile several experimental research findings that show sustained shifts towards OS will alter the homeostatic redox mechanism to cause cardiovascular complications, as well as findings that show a prolonged antioxidant state or RS can similarly lead to such cardiovascular complications. This experimental evidence is specifically focused on the role of glutathione, the most abundant antioxidant in the heart, in a redox homeostatic mechanism that has been shifted towards OS or RS. This may lead to impairment of cellular signaling mechanisms and elevated pools of proteotoxicity associated with cardiac dysfunction.